Development of an Albumin-Based PSMA Probe With Prolonged Half-Life - Liu, Teli; Liu, Chen; Ren, Yanan; Guo, Xiaoyi; Jiang, Jinquan; Xie, Qing; Xia, Lei; Wang, Feng; Zhu, Hua; Yang, Zhi (Frontiers in Molecular Biosciences, 2020)
Prostate specific membrane antigen (PSMA) is an attractive target for the diagnosis and therapy of prostate cancer as it is specifically over-expressed in prostate cancer cells. Improving the circulation of radioligand in blood is thought to improve the tumor burden, which is benefit for the detecting of small lesions and improving the effect of PSMA radioligand therapy (PRLT). In this study, we introduced Maleimidopropionic acid (MPA) to PSMA targeted tracer and developed Al18F-PSMA-CM, which was human serum albumin (HSA) binding and PSMA targeted. Al18F-PSMA-CM is evaluated in vitro and in vivo for stability, PSMA specificity and biodistribution in 22Rv1 tumor bearing mice. Al18F-PSMA-CM was prepared with the radiochemical purity of >99% and the specific activity of 11.22-18.70 MBq/nmol. It was stable in vitro and in vivo and bound to HSA with higher binding ratio (47±3.2%) with prolonged circulation in blood. The uptake of Al18F-PSMA-CM in PSMA+ 22Rv1 cells was increased in 2 h and the uptake was blocked by PSMA inhibitor, ZJ-43 (2.58±0.19 to 1.72±0.14 IA%/106 cells at 2 h). Al18F-PSMA-CM was accumulated in kidneys and 22Rv1 tumors (74.76±15.42 and 6.16±0.74 ID%/g at 4 h p.i.), which was blocked by co-injection of ZJ-43 (-80.0% and -84.3%). Al18F-PSMA-CM showed high PSMA specificity and typical biological properties of PSMA targeted tracers. As the MPA moiety showed the ability to prolong the half-life of tracer, it may be a choice to develop radiopharmaceuticals for PRLT of prostate cancer.